COMPARATIVE ANALYSIS OF THE FINANCIAL PERFORMANCE OF PT. INDIKA ENERGY Tbk BEFORE AND AFTER THE ESTABLISHMENT OF POLICY LAW NO 11 OF 2020 CONCERNING CREATION OF WORK RELATED TO THE DETERMINATION OF COAL AS AN OBJECT OF VALUE ADDED TAX - Agung Prihandoko; Dudi Rianto (Sean Institute, 2023)
This study aims to determine how the financial performance of PT. Indika Energy Tbk and what is the projection of the Development of the state Treasuries for the stipulation of the Coal commodity as a Goods Object subject to Value Added Tax (VAT) before and after the provisions in the Job Creation Law . The method used in this thesis uses a quantitative descriptive research method. From this study it was concluded that the Financial performance of PT. Indika energy Tbk showed good performance. comparison of Financial performance before and after the implementation of the Job Creation Law shows that from the Profit and Loss reports, US well US Profitability ratios have increased. The development of the state treasury experienced a decrease in the impact of this policy. If the government continues to implement this policy, the potential for a reduction in state revenues from the coal sector will have a significant impact, this is certainly inversely proportional to the government's expectation to increase the added value of state revenues from coal commodities from the taxes sector.